TELAAH TEORITIS FINITE STATE AUTOMATA DENGAN PENGUJIAN HASIL PADA MESIN OTOMATA - Widyasari widyasari (SISFOTENIKA, 2011)
Abstracts: Otomata and language theory cannot be separated in the world of informatics and represents compulsory subjects that must be provided. Therefore, to produce software in engineering requires a model which can be the solution of a problem later, because the model is an idea that will be applied to generate a software engineering. As one model that mean in here is otomata machine which is the model that can recognize, accept/ generate a sentence in a particular language. It is necessary to understand how to do modeling and testing so that it can be concluded on otomata engine if the string entered correct or wrong. This study will only discuss about the correctness of the theory of otomata machine. The benefits of this research are expected to provide input in order to prove the truth of a study. From the results, some conclusions that prove the truth of the review. Keywords: Automata, FSA, DFA, NFA.